The Impact of Green Supply Chain Management on the Environmental Performance in Private Companies of Bangkok: Mediating Role of Green Innovation - Worasatepongsa, Pornpawee; Chordkunpan, Aittichord; Jermsittiparsert, Kittisak (ExcelingTech, 2020)
The environmental performance is an essential element for the success of the organization and this could be attained by employing the effective green supply chain practices and its management. Thus, the ongoing study aims to explore the nexus among the green supply chain management (internal environment management, reverse logistic, green purchasing and customer environmental corporation) and environmental performance of the private organizations in Bangkok Thailand. The purpose of the study is also to examine the mediating role of green innovation among the practices of green supply chain management and environmental performance of the private organization in Thailand. The primary data has been obtained by the researchers from the employees that are associated with the management of the green supply chain by using questionnaires and PLS-SEM has been executed for analysis. The results of the present study exposed that the management of the green supply chain has positive along with significant nexus with the environmental performance of the private organization in Bangkok. The results also indicated that green innovation has also positively mediating among the links of management of supply chain and environmental performance of the private firm in Bangkok. These findings have provided the guidelines to the environmental regulation developing authorities that they should spend more intention on the green supply chain that could improve the performance of the environment that is necessary for the success of the organization.